Training on Food Processing Based on Local Food Kersen Leaves to Encourage a Healthy Lifestyle - Sephia Dewi, Devani; Hasanah, Dinda Nuraini; Agustina, Risma Alfi; Rahmadani, Nadya Anisa; Primastuti, Ade Martha (Yayasan Putra Adi Dharma, 2024)
Indonesian people are increasingly consuming unhealthy food due to increasing demand for ready-to-eat food. Kersen leaves are a healthy food substitute that can be used to make chips. Kersen leaves have many health benefits. In Jumoyo Village, Magelang Regency, this training was held to educate the local community about the production of kersen leaf chips and promote the health benefits of these snacks. Several stages of this training include explaining the benefits of kersen leaves for health, preparing materials and equipment, carrying out chip making, and ending with an evaluation. The results of this training show an increase in community knowledge regarding local food processing and creating business opportunities. Kersen leaf chips have the potential to be a nutritious snack that is safe to consume and can help people live healthy lives.